IDRA weather radar measurements - day 2017-11-13 - H.W.J.(Herman) Russchenberg; C.M.H.(Christine) Unal; J.(Jiapeng) Yin (TU Delft, 2018)
Radar range: far. Max rain level: moderate rain.
Parent item:
IDRA weather radar measurements - month 2017-11
Measuring instrument:
IDRA atmospheric radar in CESAR observatory, Cabauw
IRCTR has built a high resolution radar system, IDRA (IRCTR Drizzle Radar), aimed at the detailed observation of the spatial and temporal distribution of rainfall and drizzle. The system was placed at the end of August 2007 on top of a 213 m high meteorological tower in the CESAR (Cabauw Experimental Site for Atmospheric Research) observatory in Cabauw, The Netherlands. This location has several advantages: In the first place, an increased sensitivity due to the reduction of the influence of ground clutter. Secondly, it allows direct observation of the horizontal distribution of low level clouds and fog. Finally, the presence of other instruments in the vicinity enhances the understanding of the physical processes in the atmosphere by synergistically combining their measurements. Data from other instruments at CESAR are available at {http://www.cesar-database.nl}.

IDRA provides the horizontal distribution of reflectivity, mean Doppler velocity, Doppler spectrum width and polarimetric parameters like differential reflectivity, linear depolarization ratio or specific differential phase. The data collected is freely available to the scientific community.
Keywords: Atmospheric Sciences; Atmosphere and Weather; Climate and Climate Change; Geomatic Engineering; Collection: Atmospheric observations IDRA, Cabauw; drizzle; polarimetric radar; precipitation; rain; weather radar; Time: 2017-11-13